Pendidikan infeksi menular seksual untuk remaja laki-laki Yogyakarta - Nadia Rahmawati; Elsi Dwi Hapsari; Wiwin Lismidiati; Nuring Pangastuti (Berita Kedokteran Masyarakat (BKM), 2018)
Adolescent boys' knowledge and health education needs about sexually transmitted infections (STIs) Purpose: To determine the knowledge of adolescent boys and the need for health education about STIs in Yogyakarta Special Region.Methods: This research is a descriptive study with cross sectional design, with a total sample of 418 male students of class XII high school. This research was conducted in the Yogyakarta Special Region High School in September-November 2017. This study used univariate, bivariate and multivariate analysis. Results: The results showed that the average age of respondents 17 years as much as 61.5%, the most sources of information were lessons at school by 67.2%, 90.7% of students living with parents and the results of knowledge of adolescent boys in DIY bad by 52.4% and good by 47.6%. External variables related to knowledge are sources of information with p = 0.001 (p <0.05), the material that young boys want to know about health education about STIs is prevention done by 81.8% and 54.8% choosing media video as the desired method.Conclusions: The role of the world of education has a very big influence in providing information about STI to boys, the collaboration between the government and related parties will increase the knowledge of boys. One effort that can be done is by educating schools, especially on preventing STIs and using audiovisual media, besides that the role of the community and family, especially parents, will greatly influence the knowledge of adolescent boys.